PROSEDUR PERHITUNGAN DAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR PADA UPT PENGELOLAAN PENDAPATAN DAERAH JEMBER - Wirahady Nur Alyansyah Mahmud (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Taxes are one of the primary sources of national and local government revenue. Local government revenue is derived in part from local taxes. Among the many types of local taxes is the Motor Vehicle Tax. In this tax, accurate calculation and payment are crucial aspects for increasing local revenue. The objective of this fieldwork is to identify and understand the procedures for calculating and paying Motor Vehicle Tax at the Jember Local Revenue Management Unit. The data used consists of qualitative data in the form of observations and interviews, as well as quantitative data in the form of Motor Vehicle Tax targets and actual collections for the years 2023–2025. The data sources used include primary data in the form of interview results and secondary data in the form of regulations related to Motor Vehicle Tax in Indonesia. The data collection methods employed include observation, interviews, literature review, and documentation related to the calculation and payment of Motor Vehicle Tax. Based on the results of the Practical Work Experience, the calculation of Motor Vehicle Tax is performed using the “Penetapan PKB & BBNKB” application. The calculation is performed by multiplying the tax base by the rate. Payment of Motor Vehicle Tax can be made offline or online by presenting the original Vehicle Registration Certificate (STNK) and the original ID card (KTP) matching the STNK. The offline payment process begins at the Registration Counter, proceeds to the Assessment Counter, and concludes at the Payment Counter/Cashier. Online payments can be made through Samsat E-Channels, such as Indomaret, Alfamart, Tokopedia, Shopee, JConnect BankJatim, and others.
PROCEDURES FOR CALCULATING AND PAYING MOTOR VEHICLE TAXES AT THE JEMBER REGIONAL REVENUE MANAGEMENT UNIT
Validasi dan Finalisasi Repositori File 02 Juli 2026_Kholif Basri
Keywords: Motor Vehicle Tax; calculation; payment